2023
DOI: 10.31762/ahj2332.0103
|View full text |Cite
|
Sign up to set email alerts
|

Review Article: Cardiac Arrhythmia among Hospitalized COVID-19 Patients

Abstract: Cardiac arrhythmia is one of the common complications among hospitalized COVID-19 patients. The incidence of arrhythmia in COVID-19 varies from 5.9% to 16.7%. This literature review to explore the epidemiology, risk factors, clinical manifestation, pathophysiology, outcomes, and management of hospitalized COVID -19 patients with cardiac arrhythmia. The literature search and review of the literature was performed on PubMed and Google Scholar from January 2020 to July 2021. Age, comorbidities, and COVID-19 dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Considering its importance in cardiovascular disease, a population-based study showed that higher ACE2 plasma levels are associated with a greater risk of severe cardiovascular disease [20]. COVID-19 has been found to increase the risk of cardiogenic shock [21,22], cardiac arrhythmias [23,24], acute myocardial injury [25,26] and sometimes sudden death in patients with cardiovascular disease [15,27,28], and at the same time, patients with cardiovascular disease have a higher risk of mortality due to COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Considering its importance in cardiovascular disease, a population-based study showed that higher ACE2 plasma levels are associated with a greater risk of severe cardiovascular disease [20]. COVID-19 has been found to increase the risk of cardiogenic shock [21,22], cardiac arrhythmias [23,24], acute myocardial injury [25,26] and sometimes sudden death in patients with cardiovascular disease [15,27,28], and at the same time, patients with cardiovascular disease have a higher risk of mortality due to COVID-19.…”
Section: Introductionmentioning
confidence: 99%